Postdigital Participation in Education How Contemporary Media Constellations Shape Participation - Weich, Andreas; Macgilchrist, Felicitas (Palgrave Studies in Educational Media,, 2023)
This open access book examines the interrelations and correlations of the postdigital condition and its relationship to education, with a particular focus on participation. Contributions reflect on how educational institutions are affected by the recent transformations of media technologies and practices, and how at the same time institutions such as schools and universities are supposed to enable people to participate in media practices in an informed and reflective way. How, and under what conditions, can teachers and students participate in contemporary media constellations? The book will be of interest to academics and researchers involved in teacher education, digital pedagogy, educational technology, instructional design, education philosophy and media education. Andreas Weich is Head of the Media / Transformation Research Department at the Leibniz Institute for Educational Media / Georg Eckert Institute, Germany. Felicitas Macgilchrist is Professor of Digital Education and Schooling at the Department of Educational Science, University of Oldenburg, Germany.